Religious Moderation in Contestation: Dynamics and Impacts of Intergroup Tensions in Karangduwur Village, Petanahan, Kebumen - Adib, Shohibul; Rosadi, Tahrir; Hanif, Muh (Indonesian Academy of Social and Religious Research (IASRR), 2025)
Religious moderation is essential for fostering harmony in pluralistic societies, yet its contestation poses significant challenges in certain communities. This study examines the dynamics of religious moderation in Karangduwur Village, Petanahan, Kebumen, where four religious groups Muhammadiyah, Nahdlatul Ulama (Moderate Islamic Group), Salafi Wahabi, and Salafi Jihadi (Conservative Islamic Group) compete within the domains of worship, education, and social institutions. Using a qualitative research methodology, data were gathered through documentation studies and content analysis to explore the drivers of contestation and their impact on communal harmony. Findings reveal that tensions arise from differing interpretations of religious moderation, ideological divides, and contested religious authority. These factors foster a community dynamic marked more by serawung kalis (together but apart) than serawung nyawiji (together but unified). Influences such as shifting religious authorities, the rise of social media, and improved education levels further amplify these challenges. The study underscores the interplay between these local dynamics and broader issues like democracy and Islamic populism in Indonesia. By highlighting the complexities of religious moderation, this research emphasizes its importance in promoting social harmony and democratic inclusivity.